Inhibitory effects of gastrin releasing peptide on gastric emptying in rats - YEGEN, BERRAK (ELSEVIER SCIENCE BV, 1996)
Gastrin-releasing peptide (GRP) has a wide range of biological actions, including stimulation of the frequency of antral contractions and delaying gastric emptying. The present study was designed to evaluate the role of GRP in the control of gastric emptying of liquid test meals in the rat. The emptying of methyl cellulose given by gavage to fasted rats, or of saline given via the fistula to conscious gastric fistula rats was not influenced by the GRP antagonists, NC-8-89 (Leu(13)-psi-(CH2NH)-Leu(14)-bombesin) and 2258U89 ((de-NH2)Phe(19),D-Ala(24),D-Pro(26)psi (CH2NH)Phe(27)(-GRP (19-27)), at 2 mg/kg, s.c. However, both antagonists (0.02, 0.2 and 2 mg/kg) reversed the inhibitory effect of HCl on gastric emptying in gastric fistula rats (P < 0.05-0.001). When peptone was administered after a preload, but not otherwise, the inhibition of emptying was also partly reversed by both antagonists at all doses used (P < 0.05-0.001). Interestingly, the delay in the emptying of hyperosmolal saline compared to saline, was enhanced at a dose of 0.2 mg/kg of both antagonists (P < 0.05 and P < 0.01). Food intake did not change significantly with the two lower doses of antagonists, but was decreased by the highest dose of NC 8-89. We conclude that GRP specifically inhibits gastric emptying of acid and peptone solutions in the conscious rat.
Keywords: gastrin-releasing peptide; gastric emptying; peptone; HCl; BOMBESIN RECEPTOR ANTAGONISTS; PRIMARY CULTURE; CONSCIOUS CATS; CHOLECYSTOKININ; CELLS; RELAXATION; STIMULATION; SECRETION; MOTILITY; MEDIATOR